Hybrid particle swarm optimization and black stork foraging for functional neural fuzzy network learning enhancement [electronic resource] - Zakria A. Ahmed, 1981- (2012)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2012